2013
DOI: 10.5336/medsci.2011-27807
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Designed Chitosan Based Hydrogel Which is Capable of Consecutively Controlled Release of TGF-Beta 1 and BMP-7

Abstract: A AB BS ST TR RA AC CT T O Ob bj je ec ct ti iv ve e: : Both Bone Morphogenetic Protein 7 (BMP-7) and Transforming Growth Factor Beta 1 (TGF-β1) have stimulating effects on chondrocyte proliferation. These growth factors act at different time points of the biological repair process. We aimed to design a hydrogel, which would enable consecutive controlled release of the growth factors. M Ma at te er ri ia al l a an nd d M Me et th ho od ds s: : We designed a chitosan particle impregnated Poly (vinylalcohol) (PV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 53 publications
0
28
0
Order By: Relevance
“…However, it is not sufficient for the development of chondrocyte and other cells alone. 4,7 For this reason, FBS and ITS should also be added to RPMI-1640 or DMEM medium in order to proliferate healthy, high confluent cells in chondrocyte cultures. 7,8 FBS contains the essential extracellular matrix proteins for cellular adhesion and provides relevant hormones, enzymes, and growth factors for cellular proliferation.…”
Section: Minimum Requirements For a Cell Culture Laboratorymentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is not sufficient for the development of chondrocyte and other cells alone. 4,7 For this reason, FBS and ITS should also be added to RPMI-1640 or DMEM medium in order to proliferate healthy, high confluent cells in chondrocyte cultures. 7,8 FBS contains the essential extracellular matrix proteins for cellular adhesion and provides relevant hormones, enzymes, and growth factors for cellular proliferation.…”
Section: Minimum Requirements For a Cell Culture Laboratorymentioning
confidence: 99%
“…PS concentration could be increased in transfer medium up to 5%, but it should be noted that antibiotics have antiproliferative effects on human tissue also. 4,7,8 ITS will stimulate cell proliferation while decreasing substantially the serum requirements for culture of many cell types. Basal media supplemented with support proliferation of chondrocyte cultures.…”
Section: Minimum Requirements For a Cell Culture Laboratorymentioning
confidence: 99%
“…Thus, this biocompatible hydrogel with more stable cross-links was obtained, which behaves like an osmotic pump and maintains the controlled release of PRP. [10] Hydrogel prepared with PRP in this manner is suitable for surgical applications, and at the application area, this hydrogel lasts 21 days with no degradation. Hydrogel and chondrocyte co-culture P-PRP Group 5…”
Section: Methodsmentioning
confidence: 99%
“…Recent well-proved studies have reported that half-life of growth factors is maximum 2 min. [37][38][39][40] It was emphasized that when growth factors -with protein and peptide structure -in PRP obtained from human were applied after that period, bioactivity decreased and even vanished. [37][38][39][40] When the studies in which PRP was obtained from autologous blood in clinics were considered, it was found that it was prepared from 10 to 20 min.…”
Section: -2234mentioning
confidence: 99%
“…[37][38][39][40] It was emphasized that when growth factors -with protein and peptide structure -in PRP obtained from human were applied after that period, bioactivity decreased and even vanished. [37][38][39][40] When the studies in which PRP was obtained from autologous blood in clinics were considered, it was found that it was prepared from 10 to 20 min. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Nevertheless, it takes time to apply it to cases, which makes its bioactive and effective treatment results controversy.…”
Section: -2234mentioning
confidence: 99%